Blue-light-excited near-infrared fluorescent material, preparation method thereof and light-emitting device
Through high entropy design and hydrothermal synthesis, the problem of low luminescence efficiency of near-infrared phosphor caused by Cr3+ doping ions in the prior art was solved, and efficient and thermally stable near-infrared fluorescent materials were realized, which expanded its near-infrared fluorescent materials in the near-infrared Applications in the infrared field.
Patent Information
- Application Number
- CN202411187016.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-27
AI Technical Summary
The prior art is difficult to obtain broadband near-infrared phosphors with good thermal quenching resistance and high luminescence efficiency at the same time. Especially due to the parity inhibition of Cr3+, its transition rate is small, making it difficult to improve luminescence efficiency, and from blue light to The large Stokes displacement of near-infrared light adds to this challenge.
The fluoride matrix system was introduced by a high entropy design, which adjusted the local structure of luminescent elements and stoichiometric ratios, reduced structural symmetry, improved quantum efficiency, and ensured the stable doping of Cr3+ ions by hydrothermal synthesis method. Improve the thermal stability and spectral width of fluorescent materials.
It has achieved efficient quantum efficiency improvement and thermal stability maintenance of near-infrared fluorescent materials, broadened its application potential in the near-infrared field, and provided excellent comprehensive performance.
Smart Images

Figure CN119144331A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of luminescent materials, and in particular relates to a near-infrared fluorescent material excited by blue light and a preparation method thereof, as well as a luminescent device. Background Art
[0002] Since near-infrared light has the remarkable ability to penetrate biological tissues and is absorbed by certain substances (covering the characteristic absorption signals of normal vibration modes of CH, OH and NH), it is widely used in food ingredient analysis, plant lighting, biomedical imaging and night vision. Compared with traditional near-infrared light sources and near-infrared LEDs, the combination of blue LEDs and broadband near-infrared phosphors will be an ideal way to build a miniaturized, portable, energy-saving and efficient near-infrared light source. Its production equipment and technology are basically the same as those of white light LEDs, which can effectively reduce R&D and production costs and make technology promotion easier.
[0003] At present, the active ions that can achieve near-infrared emission mainly include rare earth ions and transition metal ions. 3+ With its unique luminescence properties (it exhibits broadband excitation and tunable near-infrared emission in an octahedral weak crystal field environment), it stands out among many ions and becomes the main doping ion of near-infrared phosphors. In recent years, some near-infrared luminescent materials with excellent performance have been reported, such as: Ca3Sc2Si3O 12 :Cr 3+ 、Na3Al2Li3F 12 :Cr 3+ and Cs2NaGaF6:Cr 3+ However, due to Cr 3+ The parity-forbidden dd electron transition determines that its transition rate is small, making it difficult to improve the luminescence efficiency. In addition, the large Stokes shift from blue light to near-infrared light makes it still quite challenging to simultaneously obtain broadband near-infrared phosphors with good thermal quenching resistance and high luminescence efficiency. Summary of the invention
[0004] The purpose of the present application is to provide a blue light excited near-infrared fluorescent material and a preparation method thereof, as well as a light-emitting device, aiming to solve the problem of simultaneously obtaining near-infrared phosphors with good luminous efficiency.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect, the present application provides a near-infrared fluorescent material excited by blue light, including a chemical formula of A2BM 1- x F6:xCr 3+ 、ACM 1-x F6:xCr3+ and A3B3M 2-x F 12 :xCr 3+ A compound of at least one of the following, wherein: the A position includes at least one of a monovalent alkali metal element and an ammonium ion group; the B position includes at least one of a monovalent alkali metal element and an ammonium ion group; the C position includes at least one of a divalent alkaline earth metal element; the M position includes at least four elements of Zn, Mg, Al, Ga, Sc, In, Ti, Zr, Hf, Sn, Ge, Y, Gd, La, Lu and Sb; the molar percentage of each element contained in the M position is close, and the molar percentage of each element is within the range of 5% to 35%; 0.01≤x≤0.35.
[0007] This application introduces high entropy design into the fluoride matrix system, enriches the selectivity of the constituent elements and stoichiometric ratios, and adjusts the local structure of the luminescent unit (i.e. [CrF6] 3- Octahedron can be induced to distort the octahedron by introducing components with different ionic radii, thereby reducing its structural symmetry and ultimately affecting its optical properties). It can effectively improve the quantum efficiency of near-infrared fluorescent materials, broaden the spectrum and move the emission peak wavelength to the long wave, and the thermal stability can also be maintained at a high level. The excellent comprehensive performance is conducive to expanding its application in the near-infrared field.
[0008] In a second aspect, the present application provides a method for preparing a blue light-excited near-infrared fluorescent material, which comprises the following steps: obtaining raw material components according to the stoichiometric ratio of the chemical formula in the above-mentioned blue light-excited near-infrared fluorescent material; the raw material components include a Cr element raw material component, an M-position raw material component and an A-position raw material component, and also include a B-position raw material component and / or a C-position raw material component; the raw material components are subjected to hydrothermal treatment to prepare the blue light-excited near-infrared fluorescent material.
[0009] The present application adopts the hydrothermal method, which is relatively simple and has high synthesis efficiency. The hydrothermal method can provide a mild synthesis environment and improve the ion diffusion rate. The long-term supercritical high temperature reaction environment under hydrothermal conditions can produce sufficient reaction activity to ensure that the reaction is sufficient and the Cr 3+ The ions are stably and effectively doped into the matrix lattice. In addition, it is safer under closed hydrothermal conditions due to the long-term use of toxic fluorine-containing acidic aqueous solutions.
[0010] In a third aspect, the present application provides a light-emitting device, comprising a light source and a light-emitting material excited by the light source, wherein the light-emitting material comprises the above-mentioned near-infrared fluorescent material excited by blue light, or comprises the near-infrared fluorescent material excited by blue light obtained by the above-mentioned preparation method.
[0011] The near-infrared fluorescent material provided in the present application or the prepared near-infrared fluorescent material has high luminous efficiency and its thermal stability can also be maintained at a high level. The excellent comprehensive performance is conducive to expanding its application in the near-infrared field. Therefore, the light-emitting device has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0013] Figure 1 This is a near-infrared pc-LED device and electroluminescence spectrum prepared in Example 10 of the present application.
[0014] Figure 2 It is a single matrix sample Cs2NaGaF6:0.20Cr 3+ and high entropy sample Cs2NaMF6:0.20Cr 3+ Excitation and emission spectra.
[0015] Figure 3 It is the high entropy sample Cs2NaMF6:0.20Cr provided in Example 4 of this application 3+ The morphology and distribution diagram of each element. Figure 3 (a) shows the morphology at a scale of 10 μm. Figure 3 (b) shows the morphology at a scale of 3 μm. Figure 3 (c) shows the element distribution diagram of the sample. Figure 3 (d) shows the Cs element distribution diagram of the sample. Figure 3 (e) shows the F element distribution diagram of the sample. Figure 3 (f) shows the Na element distribution diagram of the sample. Figure 3 (g) shows the Ga element distribution diagram of the sample. Figure 3 (h) shows the Cr element distribution diagram of the sample. Figure 3 (i) shows the Al element distribution diagram of the sample. Figure 3 (j) shows the In element distribution diagram of the sample. Figure 3 (k) in the middle shows the Sc element distribution diagram of the sample.
[0016] Figure 4 It is a single matrix sample Cs2NaGaF6:0.20Cr 3+ and high entropy sample Cs2NaMF6:0.20Cr 3+ Raman spectrum of .
[0017] Figure 5 It is a matrix-like Cs2NaGaF6:0.20Cr 3+ and high entropy sample Cs2NaMF6:0.20Cr 3+ The crystal structure diagram of Figure 5 (a) represents Cs2NaGaF6:0.20Cr 3+ The crystal structure diagram of Figure 5 (b) represents Cs2NaGaF6:0.20Cr 3+ The coordination environment of each cation, Figure 5 (c) represents Cs2NaGaF6:0.20Cr 3+ Schematic diagram of the layered structure, Figure 5 (d) indicates Cs2NaMF6:0.20Cr 3+ The crystal structure diagram of Figure 5 (e) indicates Cs2NaMF6:0.20Cr 3+ Schematic diagram of the layered structure, Figure 5 (f) indicates Cs2NaMF6:0.20Cr 3+ The coordination environment of each cation.
[0018] Figure 6 The different Cr provided in Example 5 of the present application 3+ XRD patterns of high entropy samples under different doping levels. Figure 6 In the table, "Calculated Cs2NaGaF6" means the calculated standard Cs2NaMF6:0.20Cr 3+ Phase cards. Since there is no known standard card, this application uses a phase card that matches each diffraction peak well and is compatible with the high entropy fluoride near-infrared phosphor Cs2NaMF6:Cr 3+ The CIF file of the same structure Cs2NaGaF6 is the basic model ( ICSD 55698), and then the model was replaced and modified by the crystal structure visualization software VESTA, and the theoretical model of Cs2NaMF6 high entropy fluoride with the same crystal structure was constructed, and finally the corresponding theoretical standard card (Calculated Cs2NaMF6 ) for analysis and comparison.
[0019] Figure 7 Single matrix sample Cs2KGaF6:0.20Cr 3+ and high entropy sample Cs2KMF6:0.20Cr 3+ The emission spectrum of .
[0020] Figure 8 High entropy sample Cs2K(Al 0.30 ,Ga0.30 ,In 0.2 ,Sc 0.2 ) 0.80 F6:0.20Cr 3+ The three-dimensional crystal structure of . DETAILED DESCRIPTION
[0021] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0022] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0023] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0024] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0025] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0026] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0027] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0028] In a first aspect, the present invention provides a near-infrared fluorescent material excited by blue light, including a chemical formula of A2BM 1-x F6:xCr 3+ 、ACM 1-x F6:xCr 3+ and A3B3M 2-x F 12 :xCr 3+ At least one compound of
[0029] The A position includes at least one of a monovalent alkali metal element and an ammonium ion group;
[0030] The B position includes at least one of a monovalent alkali metal element and an ammonium ion group;
[0031] The C position includes at least one of the divalent alkaline earth metal elements;
[0032] The M position includes at least four elements of Zn, Mg, Al, Ga, Sc, In, Ti, Zr, Hf, Sn, Ge, Y, Gd, La, Lu and Sb; the molar percentage of each element included in the M position is close, and the molar percentage of each element is in the range of 5% to 35%;
[0033] 0.01≤x≤0.35.
[0034] The present invention introduces high entropy design into the fluoride matrix system, enriches the selectivity of the constituent elements and stoichiometric ratios, and adjusts the local structure of the luminescent unit (i.e. [CrF6] 3-Octahedron can be induced to distort the octahedron by introducing components with different ionic radii, thereby reducing its structural symmetry and ultimately affecting its optical properties). It can effectively improve the quantum efficiency of near-infrared fluorescent materials, broaden the spectrum and move the emission peak wavelength to the long wave, and the thermal stability can also be maintained at a high level. The excellent comprehensive performance is conducive to expanding its application in the near-infrared field.
[0035] Unlike traditional binary solid solution systems, high entropy materials are composed of 5 or more components with close molar ratios. The selectivity and diversity of their structures, compositions and proportions expand the composition range of material design and enrich the development space of materials. At the same time, high entropy materials have high configurational entropy, which can inhibit the phase separation tendency of materials and easily obtain a single structure high entropy solid solution phase. In addition, the high entropy structural effect can induce local structural distortion and increase the disorder of the system, which is conducive to breaking the Cr 3+ The parity forbidden characteristics of dd transitions will eventually improve Cr 3+ Luminescence efficiency and performance of activated fluoride near-infrared phosphors.
[0036] The present invention introduces the high entropy design concept into the fluoride matrix system, and obtains a high entropy fluoride matrix by optimizing the composition elements and proportion design. Due to the different radii and valence states of the cations in the matrix, and the significant differences in the bond lengths and bond angles between atoms, [CrF6] 3- The degree of octahedral distortion increases, which will lead to Cr 3+ The surrounding local structure changes and the symmetry is reduced, which is conducive to breaking the Cr 3+ The parity forbidden characteristics of dd transitions will eventually improve Cr 3+ Luminescence efficiency and thermal stability of activated fluoride near-infrared phosphors.
[0037] In some embodiments, the element selection principle for the M position includes at least one of the following (1) to (4): (1) the ionic radius of each element should be as close as possible; (2) the electronegativity of the elements is similar; (3) the charge of the lattice site should be balanced; (4) the crystal structure of the corresponding matrix of each element is similar.
[0038] Inorganic phosphors are mainly composed of inorganic crystal materials as a matrix and activator ions as luminescent centers. Therefore, the above-mentioned "matrix" is specifically exemplified by A2BM 1-x F6 and ACM 1-x F6; "lattice site" refers to the M site in each matrix material, that is, the activated ion Cr 3+ replacement position.
[0039] In some embodiments, the molar percentage of each element contained in the M position is close, and the molar percentage of each element is in the range of 5% to 35%.
[0040] In some embodiments, the element or group at the A position and the element or group at the B position may be the same.
[0041] In some embodiments, the element or group at the A position is different from the element or group at the B position.
[0042] In some embodiments, at least one of the following (1) to (5) is satisfied:
[0043] (1) The monovalent alkali metal element in the A position includes at least one of Li, Na, K, Rb and Cs;
[0044] (2) the monovalent alkali metal element in the B position includes at least one of Li, Na, K, Rb and Cs;
[0045] (3) The ammonium group in position A includes at least one of an ammonium radical group and a tetramethylammonium group,
[0046] (4) the ammonium group in position B includes at least one of an ammonium radical group and a tetramethylammonium group;
[0047] (5) The divalent alkaline earth metal element includes at least one of Ca, Sr, Ba, Mg and Zn.
[0048] The ions corresponding to the monovalent alkali metal elements include Li + 、Na + , K + , Rb + and Cs + At least one of them.
[0049] The ammonium group is NH 4+ ; Tetramethylammonium group is (CH3)4N + (Tetramethylammonium, TMA + ).
[0050] Furthermore, the ions corresponding to the A position include Li + 、Na + , K + , Rb + , Cs + NH 4+ and (CH3)4N + At least one of them.
[0051] Furthermore, the ions corresponding to the B position include Li + 、Na + , K + , Rb + , Cs + NH 4+ and (CH3)4N + At least one of them.
[0052] In some embodiments, the divalent alkaline earth metal element includes at least one of Ca, Sr, Ba, Mg, and Zn.
[0053] The ions corresponding to the divalent alkali metal elements include Ca 2+ , Sr 2+ , Ba 2+ Mg 2+ and Zn 2+ At least one of them.
[0054] Furthermore, the ions corresponding to the C position include Ca 2+ , Sr 2+ , Ba 2+ Mg 2+ and Zn 2+ At least one of them.
[0055] In some embodiments, the molar percentage of each element contained in the M position differs within 10%. In a specific example, the molar percentage of each element contained in the M position differs by 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0056] In some embodiments, the wavelength of the excitation light of the near-infrared fluorescent material excited by blue light is 420nm to 470nm; and / or the wavelength of the emission light is 700nm to 1000nm.
[0057] In some embodiments, the chemical formula is A2BM 1-x F6:xCr 3+ The compound satisfies any one of the following (1) to (2):
[0058] (1) The A and B positions are both K, and the M position is a combination of four elements: Al, Ga, In, and Sc. Furthermore, the M position is Al, Ga, In, and Sc, and the corresponding molar ratio of each element is 0.30:0.30:0.20:0.20. Furthermore, x is 0.08. In this case, the chemical formula of the fluorescent material is K3(Al 0.30 ,Ga 0.30 ,In 0.20 ,Sc 0.20 ) 0.92 F6:0.08Cr 3+ .
[0059] (2) A and B are both Na, and M is a combination of five elements: Zn, Al, Ga, Sc, and Ti. Further, M is Zn, Al, Ga, Sc, and Ti, and the molar ratio of the corresponding elements is 0.20:0.20:0.20:0.20:0.20. Furthermore, x is 0.25. In this case, the chemical formula of the fluorescent material is Na3(Zn 0.20,Al 0.20 ,Ga 0.20 ,Sc 0.20 ,Ti 0.20 ) 0.75 F6:0.25Cr 3+ .
[0060] (3) A is K, B is Li, and M is a combination of five elements: Al, Ga, In, Sc, and Lu. Further, M is Al, Ga, In, Sc, and Lu, and the molar ratio of the corresponding elements is 0.20:0.20:0.20:0.20:0.20. Further, x is 0.10. In this case, the chemical formula of the fluorescent material is K2Li(Al 0.20 ,Ga 0.20 ,In 0.20 ,Sc 0.20 ,Lu 0.20 ) 0.90 F6:0.10Cr 3+ .
[0061] (4) A is Cs, B is Na, and M is a combination of four elements: Al, Ga, In, and Sc. Further, M is Al, Ga, In, and Sc, and the molar ratio of each element is 0.25:0.25:0.25:0.25. Furthermore, x is 0.20. In this case, the chemical formula of the fluorescent material is Cs2Na(Al 0.25 ,Ga 0.25 ,In 0.25 ,Sc 0.25 ) 0.80 F6:0.20Cr 3+ .
[0062] (5) A is Rb, B is K, and M is a combination of seven elements: Al, Ga, In, Y, Gd, Sc, and Lu. Further, M is Al, Ga, In, Y, Gd, Sc, and Lu, and the molar ratio of the corresponding elements is 0.15:0.15:0.15:0.10:0.15:0.15:0.15. Furthermore, x is 0.12. In this case, the chemical formula of the fluorescent material is Rb2K(Al 0.15 ,Ga 0.15 ,In 0.15 ,Y 0.10 ,Gd 0.15 ,Sc 0.15 ,Lu 0.15 ) 0.88 F6:0.12Cr 3+ .
[0063] (6) The A position is Cs, the B position is Na, and the M position is a combination of four elements: Al, Ga, In, and Sc. Furthermore, the M position is Al, Ga, In, and Sc, and the corresponding molar ratio of each element is 0.25:0.25:0.25:0.25. In this case, the chemical formula of the fluorescent material is Cs2Na(Al 0.25 ,Ga 0.25 ,In 0.25 ,Sc 0.25 ) 1-x F6:xCr 3+ .
[0064] In some embodiments, the chemical formula is ACM 1-x F6:xCr 3+ Compounds that satisfy:
[0065] A is Li, B is Sr, and M is a combination of five elements: Al, Ga, In, Gd, and Sc. Further, M is Al, Ga, In, Gd, and Sc, and the molar ratio of the corresponding elements is 0.20:0.20:0.20:0.20:0.20. Furthermore, x is 0.15. At this time, the chemical formula of the fluorescent material is LiSr(Al 0.20 ,Ga 0.20 ,In 0.20 ,Gd 0.20 ,Sc 0.20 ) 0.85 F6:0.15Cr 3+ .
[0066] In some embodiments, the chemical formula is A3B3M 2-x F 12 :xCr 3+ Compounds that satisfy:
[0067] A is Na, B is Li, and M is a combination of four elements: Al, Ga, In, and Sc. Further, M is Al, Ga, In, and Sc, and the molar ratio of each element is 0.30:0.30:0.20:0.20. Furthermore, x is 0.09. At this time, the chemical formula of the fluorescent material is Li3Na3(Al 0.30 ,Ga 0.30 ,In 0.20 ,Sc 0.20 ) 1.91 F6:0.09Cr 3+ .
[0068] A second aspect of the present application provides a method for preparing a near-infrared fluorescent material excited by blue light, which comprises the following steps:
[0069] Obtaining raw material components according to the stoichiometric ratio of the chemical formula in the above-mentioned blue light-excited near-infrared fluorescent material; the raw material components include Cr element raw material components, M-position raw material components and A-position raw material components, and also include B-position raw material components and / or C-position raw material components;
[0070] The raw material components are subjected to hydrothermal treatment to prepare a near-infrared fluorescent material excited by blue light.
[0071] The hydrothermal method used in the present application is relatively simple and has high synthesis efficiency. The hydrothermal method can provide a mild synthesis environment and increase the ion diffusion rate. The long-term supercritical high temperature reaction environment under hydrothermal conditions can produce sufficient reaction activity to ensure that the reaction is sufficient and the Cr 3+ The ions are stably and effectively doped into the matrix lattice. In addition, it is safer under closed hydrothermal conditions due to the long-term use of toxic fluorine-containing acidic aqueous solutions.
[0072] In some embodiments, the raw material components satisfy at least one of the following (1) to (5):
[0073] (1) The Cr element raw material component includes at least one of chromium chloride, chromium nitrate, chromium hydroxide, chromium fluoride and chromium oxide;
[0074] (2) The raw material component of the M position includes at least one of an oxide, a fluoride and a metal salt;
[0075] (3) The raw material component at position A includes at least one of a fluoride and a carbonate;
[0076] (4) The raw material component at position B includes at least one of a fluoride and a carbonate;
[0077] (5) The C-position raw material component includes at least one of fluoride and carbonate.
[0078] The raw material components selected in the embodiments of the present application have low cost and high solubility in the solvent, which is conducive to participating in the reaction and improving the reaction efficiency.
[0079] In the embodiment of the present application, the raw material component at the M position includes at least one of an oxide, a fluoride and a metal salt. Wherein, "fluoride" refers to a compound composed of fluoride ions and corresponding metal ions; wherein "metal salt" refers to a salt compound composed of metal ions and acid radical ions. Wherein "oxide" is an oxide formed by the above-mentioned metal ions; and the above-mentioned metal ions are metal ions corresponding to at least one element of Zn, Al, Ga, Sc, In, Ti, Y, Gd, La, Lu and Sb in the M position. Further, the metal salt includes at least one of sulfate, nitrate and carbonate.
[0080] In the present application, in the raw material component A, "fluoride" refers to fluoride ions (F- ) or hydrogen difluoride ion (HF2 - ) and a compound composed of a cationic ion. Further, the cation is an ion corresponding to a monovalent alkali metal element or an ammonium group at position A in the chemical formula. In a specific example, the fluoride includes at least one of LiF, NaF, KF, RbF, CsF, NH4F, (CH3)4NF, NH4HF2 and KHF2. The carbonate in the raw material component at position A is a carbonate corresponding to a monovalent alkali metal element or an ammonium group at position A.
[0081] In the present application, in the raw material component B, "fluoride" refers to fluoride ions (F - ) or hydrogen difluoride ion (HF2 - ) and a cation ion. Further, the cation is the ion corresponding to the monovalent alkali metal element or ammonium group at the A position in the chemical formula. In a specific example, the fluoride includes at least one of LiF, NaF, KF, RbF, CsF, NH4F, (CH3)4NF, NH4HF2 and KHF2. The carbonate in the B position raw material component is the carbonate corresponding to the monovalent alkali metal element or ammonium group at the B position.
[0082] In the embodiments of the present application, in the C-position raw material component, "fluoride" refers to fluoride ions (F - ) or hydrogen difluoride ion (HF2 - ) and metal ions. Further, the cation is the ion corresponding to the divalent alkaline earth metal element at the C position in the chemical general formula. In a specific example, the fluoride includes at least one of CaF2, CsF2, BaF2, MgF2 and ZnF2. The carbonate in the C position raw material component is the carbonate corresponding to the divalent alkali metal element at the C position.
[0083] In some embodiments, the solvent used in the hydrothermal treatment includes a fluorine-containing acidic aqueous solution.
[0084] In the embodiments of the present application, the fluorine-containing acidic aqueous solution is used to dissolve various raw materials, provide a reaction environment, and can also be used to provide a fluorine source, thereby stabilizing the generated fluoride fluorescent material.
[0085] Furthermore, the fluorine-containing acidic aqueous solution is a hydrofluoric acid aqueous solution.
[0086] Furthermore, the fluorine-containing acidic aqueous solution is an aqueous solution composed of an acid and a fluorine source. The acid includes at least one of hydrofluoric acid, nitric acid, hydrochloric acid and phosphoric acid. The fluorine source includes at least one of fluoride and hydrofluoride; the fluoride includes HF; and the hydrofluoride includes NH4HF2.
[0087] In some embodiments, the fluorine-containing acidic aqueous solution has a mass percent concentration of 10% to 49%.
[0088] In some embodiments, the parameters controlled during the hydrothermal treatment step include:
[0089] The temperature of the hydrothermal treatment is 160° C. to 240° C., and / or the time of the hydrothermal treatment is 6 h to 24 h.
[0090] The reaction temperature may affect the luminous intensity of the fluorescent material. By reasonably selecting the reaction temperature, the luminous intensity of the fluorescent material can be further improved.
[0091] In some embodiments, the step of subjecting the feedstock components to hydrothermal treatment comprises:
[0092] The order of adding the raw material components and the solvent is controlled to satisfy the following requirement: the raw material component at position A and at least one of the raw material component at position B and the raw material component at position C are added last.
[0093] The order of adding other raw material components (M raw material component, Cr element raw material component) and solvent is not limited, and it is sufficient to ensure that the A raw material component and at least one of the B raw material component and the C raw material component are added last. The A raw material component and the B raw material component, or the C raw material component, can be used as a precipitant in combination to promote the smooth progress of the reaction and generate the target product.
[0094] In the present application, for example, the preparation chemical formula is A2BM 1-x F6:xCr 3+ The compound is then added with the raw material component A and the raw material component B at the end; for example, the general chemical formula for the preparation is A3B3M 2-x F 12 :xCr 3+ The compound is then added with the raw material component A and the raw material component B at the end; if the preparation chemical formula is ACM 1-x F6:xCr 3+ If the compound is a raw material, the A-position raw material component and the C-position raw material component are added last.
[0095] In some embodiments, the step of subjecting the feedstock components to hydrothermal treatment comprises:
[0096] First, the M raw material component and the solvent used for the hydrothermal treatment are mixed; then the Cr element raw material component is added and mixed; then the A raw material component and at least one of the B raw material component and the C raw material component are added and mixed to obtain a mixed material;
[0097] The mixed material is subjected to hydrothermal treatment.
[0098] In a specific example, the preparation chemical formula is A2BM 1-xF6:xCr 3+ Compound: first add the M raw material component and the solvent used for hydrothermal treatment, and mix them; then add the Cr element raw material component, and mix them; then add the A raw material component and the B raw material component, and mix them to obtain a mixed material; and perform hydrothermal treatment on the mixed material.
[0099] In a specific example, the preparation chemical formula is ACM 1-x F6:xCr 3+ Compound: first add the M raw material component and the solvent used for hydrothermal treatment, and mix them; then add the Cr element raw material component, and mix them; then add the A raw material component and the C raw material component, and mix them to obtain a mixed material; and perform hydrothermal treatment on the mixed material.
[0100] In a specific example, the preparation chemical formula is A3B3M 2-x F 12 :xCr 3+ Compound: first add the M raw material component and the solvent used for hydrothermal treatment, and mix them; then add the Cr element raw material component, and mix them; then add the A raw material component and the B raw material component, and mix them to obtain a mixed material; and perform hydrothermal treatment on the mixed material.
[0101] In a specific example, the preparation chemical formula is A2BM 1-x F6:xCr 3+ The compound and chemical formula is ACM 1-x F6:xCr 3 + Compound: first add the M raw material component and the solvent used for hydrothermal treatment, and mix them; then add the Cr element raw material component, and mix them; then add the A raw material component, the B raw material component and the C raw material component, and mix them to obtain a mixed material; and perform hydrothermal treatment on the mixed material.
[0102] In a specific example, the preparation chemical formula is A2BM 1-x F6:xCr 3+ The compound and chemical formula is A3B3M 2-x F 12 :xCr 3+ Compound: first add the M raw material component and the solvent used for hydrothermal treatment, and mix them; then add the Cr element raw material component, and mix them; then add the A raw material component and the B raw material component, and mix them to obtain a mixed material; and perform hydrothermal treatment on the mixed material.
[0103] A third aspect of an embodiment of the present application provides a light-emitting device, comprising a light source and a light-emitting material excited by the light source, wherein the light-emitting material comprises the above-mentioned near-infrared fluorescent material excited by blue light, or comprises the near-infrared fluorescent material excited by blue light obtained by the above-mentioned preparation method.
[0104] The near-infrared fluorescent material provided in the embodiments of the present application or the prepared near-infrared fluorescent material has high luminous efficiency and its thermal stability can also be maintained at a high level. Its excellent comprehensive performance is conducive to expanding its application in the near-infrared field. Therefore, the light-emitting device has a good application prospect.
[0105] The following describes the invention in conjunction with specific embodiments.
[0106] Example 1
[0107] This embodiment provides a near-infrared fluorescent material excited by blue light, and its chemical formula is: K3(Al 0.30 ,Ga 0.30 ,In 0.20 ,Sc 0.20 ) 0.92 F6:0.08Cr 3+ , the specific preparation method is as follows:
[0108] According to the stoichiometric ratio, the corresponding raw materials were weighed: 0.1159 g AlF3, 0.1293 g Ga2O3, 0.1277 g In2O3, 0.0634 g Sc2O3, 0.0436 g CrF3 and 2.905 g KF.
[0109] First, the raw materials AlF3, Ga2O3, In2O3 and Sc2O3 were added to the reaction container in sequence; then 6 mL HF was added and mechanically stirred for 10 min; then CrF3 was added and stirred for 5 min; then KF was added to the above solution and stirred for 25 min at room temperature.
[0110] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, and kept at 160°C for 12 h.
[0111] After the reaction was completed and cooled to room temperature, the green product was collected and washed three times with 25 mL of acetic acid and anhydrous ethanol respectively. Finally, it was placed in a drying oven at 65 ° C for 6 h. Finally, the high entropy sample was obtained, which was the near-infrared fluorescent material K3 (Al 0.30 ,Ga 0.30 ,In 0.20 ,Sc 0.20 ) 0.92 F6:0.08Cr 3+ , abbreviated as K3MF6:0.08Cr 3+ .
[0112] Example 2
[0113] This embodiment provides a near-infrared fluorescent material excited by blue light, and its chemical formula is: Na3(Zn 0.20 ,Al 0.20 ,Ga 0.20 ,Sc 0.20 ,Ti 0.20 ) 0.75 F6:0.25Cr 3+ , the specific preparation method is as follows:
[0114] According to the stoichiometric ratio, the corresponding raw materials were weighed: 0.2813 g Al(NO3)3·9H2O, 0.0703 g Ga2O3, 0.0517 g Sc2O3, 0.0611 g ZnO, 0.0599 g TiO2, 0.2752 g (NH4)3CrF6 and 0.6299 g NaF.
[0115] First, the raw materials Al(NO3)3·9H2O, Ga2O3, Sc2O3, ZnO and TiO2 were added to the reaction container in sequence; then 6 mL of HF was added and mechanically stirred for 15 min; then (NH4)3CrF6 was added and stirred for 5 min; then NaF was added to the above solution and stirred at room temperature for 20 min.
[0116] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, and kept at 200°C for 10 h.
[0117] After the reaction was completed and cooled to room temperature, the green product was collected and washed three times with 20 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a 60 ° C drying oven for 8 h. Finally, the high entropy sample was obtained, which was the blue light excited near-infrared fluorescent material Na3(Zn 0.20 ,Al 0.20 ,Ga 0.20 ,Sc 0.20 ,Ti 0.20 ) 0.75 F6:0.25Cr 3+ , abbreviated as Na3MF6:0.25Cr 3+ .
[0118] Example 3
[0119] This embodiment provides a near-infrared fluorescent material excited by blue light, and its chemical formula is: K2Li(Al 0.20 ,Ga 0.20 ,In 0.20 ,Sc 0.20 ,Lu 0.20 ) 0.90 F6:0.10Cr 3+, the specific preparation method is as follows:
[0120] According to the stoichiometric ratio, the corresponding raw materials were weighed: 0.0756 g AlF3, 0.0843 g Ga2O3, 0.1249 g In2O3, 0.0621 g Sc2O3, 0.1791 g Lu2O3, 0.2001 g Cr(NO3)3·9H2O, 0.7810 g KHF2 and 0.1297 g LiF.
[0121] First, add the raw materials AlF3, Ga2O3, In2O3, Sc2O3 and Lu2O3 into the reaction container; then add 5mL HF and stir for 5 minutes; then add Cr(NO3)3·9H2O and continue stirring for 15 minutes; then add KHF2 and LiF to the above solution in sequence and continue stirring at room temperature for 30 minutes.
[0122] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus and kept at 180°C for 15 h.
[0123] After the reaction was completed and cooled to room temperature, the green product was collected and washed three times with 25 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 65 ° C for 8 h. Finally, the high entropy sample was obtained, which was the near-infrared fluorescent material K2Li (Al 0.20 ,Ga 0.20 ,In 0.20 ,Sc 0.20 ,Lu 0.20 )0.90F6:0.10Cr 3+ , abbreviated as K2LiMF6:0.10Cr 3+ .
[0124] Example 4
[0125] This embodiment provides a near-infrared fluorescent material excited by blue light, and its chemical formula is: Cs2Na(Al 0.25 ,Ga 0.25 ,In 0.25 ,Sc 0.25 ) 0.80 F6:0.20Cr 3+ , the specific preparation method is as follows:
[0126] According to the stoichiometric ratio, the corresponding raw materials 0.0420 g AlF3, 0.0469 g Ga2O3, 0.0694 g In2O3, 0.0345 g Sc2O3, 0.20 g Cr(NO3)3·9H2O, 0.1050 g NaF and 7.595 g CsF were weighed.
[0127] First, add the raw materials AlF3, Ga2O3, In2O3 and Sc2O3 into the reaction container, then add 5 mL HF and stir for 10 minutes; then add Cr(NO3)3·9H2O and continue stirring for 25 minutes; then add NaF and CsF to the above solution in sequence and continue stirring at room temperature for 40 minutes.
[0128] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, where it was kept at 200°C for 18 h.
[0129] After the reaction was completed and cooled to room temperature, the green product was collected and washed three times with 25 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 70 ° C for 6 h. Finally, the high entropy sample was obtained, which was the near-infrared fluorescent material Cs2Na(Al 0.25 ,Ga 0.25 ,In 0.25 ,Sc 0.25 ) 0.80 F6:0.20Cr 3+ , abbreviated as Cs2NaMF6:0.20Cr 3+ .
[0130] Example 4 Preparation of high entropy sample Cs2NaMF6:0.20Cr 3+ The excitation and emission spectra of Figure 2 The morphology and element distribution are shown in Figure 3 The quantum efficiency is shown in Table 1.
[0131] Table 1 Quantum efficiency
[0132] sample IQE(%) AE(%) EQE(%) <![CDATA[Cs2NaGaF6:0.20Cr 3+ ]]> 85.7 26.1 22.37 <![CDATA[Cs2NaMF6:0.20Cr 3+ ]]> 97 27.3 26.5
[0133] Note: In Table 1, “IQE” stands for internal quantum efficiency, “AE” stands for x-absorption, and “EQE” stands for external quantum efficiency.
[0134] like Figure 2 As shown, three typical excitation bands can be observed in the visible light region, among which the strong excitation band centered at 437nm dominates the excitation spectrum, indicating that Cs2NaGaF6:0.20Cr 3+ and Cs2NaMF6:0.20Cr 3+ The phosphor can be effectively excited by the commercial InGaN blue light chip. Under 437nm excitation, the single matrix Cs2NaGaF6:0.20Cr 3+A wide near-infrared emission band with a peak at 789nm was obtained in the range of 650nm to 1100nm, and its FWHM was 117nm. After the Ga site high entropy design, the disorder of the high entropy phosphor increased, resulting in enhanced electron-phonon coupling, thereby broadening the emission band. In addition, Cs2NaMF6:0.20Cr 3+ The emission peak wavelength is red-shifted from 789nm to 795nm, and the integrated emission intensity is significantly higher than that of the single matrix Cs2NaGaF6:0.20Cr 3+ The improvement is 65.3%, which can be attributed to the high entropy design of Cs2NaMF6:0.20Cr 3+ Medium Cr 3+ The symmetry of the crystal field environment is reduced. Under this condition, Cr 3+ The dd transition probability is enhanced, thereby improving near-infrared emission.
[0135] like Figure 3 , the morphology images show that the samples have high compositional homogeneity, confirming the successful synthesis of single-phase high-entropy fluorides.
[0136] In addition, the high entropy sample Cs2NaMF6:0.20Cr 3+ With single matrix Cs2NaGaF6:0.20Cr 3+ Raman spectrum
[0137] like Figure 4 As shown, Cs2NaMF6:0.20Cr 3+ With Cs2NaGaF6:0.20Cr 3+ The Raman spectrum curves of Cs2NaMF6:0.20Cr 3+ With Cs2NaGaF6:0.20Cr 3+ Similar vibration modes. But there are differences between the two. First, Cs2NaMF6:0.20Cr 3+ At 150cm -1 ~300cm -1 The A1g mode in the Ga-based quartz crystal shifts to a lower wavenumber, which can be attributed to the elongation of its related chemical bonds. Therefore, it can be considered that after the high entropy design at the Ga site, the increase in the lattice parameter caused by the increase in the average cation ion radius ultimately leads to the shift of the Raman peak. 3+ Compared with Cs2NaMF6:0.20Cr 3+ In the low frequency region (150cm -1 ~300cm -1 ) showed obvious broadening of the Raman peak at ~223cm -1A new low-frequency mode appears at the high entropy design, which indicates that the structural disorder increases after high entropy design and the high entropy fluoride Cs2NaMF6:0.20Cr 3+ It has severe lattice distortion, which is beneficial to enhancing the luminescence effect.
[0138] like Figure 5 Single matrix Cs2NaGaF6:0.20Cr 3+ and high entropy sample Cs2NaMF6:0.20Cr 3+ Crystal structure diagram. 3+ Similar, Cs2NaMF6:0.20Cr 3+ The crystal framework is composed of [NaF6] octahedron, [MF6] octahedron and [CsF 12 ] polyhedrons, among which [NaF6] octahedrons and [MF6] octahedrons are stacked and arranged along the c-axis to form a three-dimensional layered framework. High entropy design is carried out at the Ga site, and multiple principal elements are introduced, which has a negligible effect on the overall crystal structure. In addition, Figure 5 As shown in (c), in a single matrix, adjacent Cr 3+ The minimum distance between ions is The maximum distance is The adjacent layer Cr 3+ The minimum distance between ions is At this time, the [CrF6] octahedra are fully separated, and the separation distance is In high entropy samples (such as Figure 5 As shown in (e), in the same layer, Cr 3+ -Cr 3+ The shortest distance between The longest distance is Adjacent layer Cr 3+ -Cr 3+ The shortest distance between Obviously, in the high entropy sample, due to the local structural modification caused by the high entropy of Ga sites, the Cr 3+ -Cr 3+ The distance between the octahedra is farther, and the distribution between the [CrF6] octahedra is more sparse. The structural constraint effect is more obvious, so it can partially inhibit Cr 3+ The non-radiative relaxation of the emission center can improve the luminescence efficiency of the fluoride near-infrared phosphor. Therefore, the luminescence efficiency of the phosphor can be effectively improved through reasonable high entropy design.
[0139] Example 5
[0140] This embodiment provides a near-infrared fluorescent material excited by blue light, and the chemical formulas are: Cs2Na(Al0.25 ,Ga 0.25 ,In 0.25 ,Sc 0.25 ) 0.70 F6:0.30Cr 3+ 、Cs2Na(Al 0.25 ,Ga 0.25 ,In 0.25 ,Sc 0.25 ) 0.75 F6:0.25Cr 3+ 、Cs2Na(Al 0.25 ,Ga 0.25 ,In 0.25 ,Sc 0.25 ) 0.80 F6:0.20Cr 3+ 、Cs2Na(Al 0.25 ,Ga 0.25 ,In 0.25 ,Sc 0.25 ) 0.85 F6:0.15Cr 3+ 、Cs2Na(Al 0.25 ,Ga 0.25 ,In 0.25 ,Sc 0.25 ) 0.90 F6:0.10Cr 3+ and Cs2Na(Al 0.25 ,Ga 0.25 ,In 0.25 ,Sc 0.25 ) 0.95 F6:0.05Cr 3+ .
[0141] The specific preparation method is the same as that of Example 4, except that the amount of the raw material Cr(NO3)3·9H2O added is changed according to the stoichiometric ratio. The abbreviations of the prepared high entropy samples are Cs2NaMF6:0.05Cr 3+ 、Cs2NaMF6:0.10Cr 3+ 、Cs2NaMF6:0.15Cr 3+ 、Cs2NaMF6:0.20Cr 3+ 、Cs2NaMF6:0.25Cr 3+ and Cs2NaMF6:0.30Cr 3+ .
[0142] The XRD diffraction patterns of the high entropy samples provided in Example 5 are as follows: Figure 6 The diffraction peaks of all samples are consistent with the theoretical standard card (Calculated Cs2NaMF6(R3 _m)) is highly matched, and no impurity phase is observed. This result shows that Cr 3+ Entering into the Cs2NaMF6 matrix lattice does not change its crystal structure.
[0143] Example 6
[0144] This embodiment provides a near-infrared fluorescent material excited by blue light, and its chemical formula is: Rb2K(Al 0.15 ,Ga 0.15 ,In 0.15 ,Y 0.10 ,Gd 0.15 ,Sc 0.15 ,Lu 0.15 ) 0.88 F6:0.12Cr 3+ , the specific preparation method is as follows:
[0145] According to the stoichiometric ratio, the corresponding raw materials were weighed: 0.2476 g Al(NO3)3·9H2O, 0.0619 g Ga2O3, 0.0916 g In2O3, 0.0455 g Sc2O3, 0.0497 g Y2O3, 0.1197 g Gd2O3, 0.1313 g Lu2O3, 0.2401 g Cr(NO3)3·9H2O, 0.2905 g KF and 1.1548 g Rb2CO3.
[0146] First, add Al(NO3)3·9H2O, Ga2O3, In2O3, Sc2O3, Y2O3, Gd2O3 and Lu2O3 to the reaction container; then add 8mL HF and stir for 15 minutes; then add Cr(NO3)3·9H2O and continue stirring for 10 minutes, then add KF and Rb2CO3 to the above solution in turn, and continue stirring at room temperature for 50 minutes.
[0147] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, where it was kept at 220°C for 12 h.
[0148] After the reaction was completed and cooled to room temperature, the green product was collected, washed twice with 30 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 75 ° C for 5 h. Finally, the high entropy sample was obtained, which was the near-infrared fluorescent material Rb2K(Al 0.15 ,Ga 0.15 ,In 0.15 ,Y 0.10 ,Gd 0.15 ,Sc 0.15 ,Lu 0.15 ) 0.88 F6:0.12Cr 3+ , abbreviated as Rb2KMF6:0.12Cr3+ .
[0149] Example 7
[0150] This embodiment provides a near-infrared fluorescent material excited by blue light, and its chemical formula is: Cs2K(Al 0.30 ,Ga 0.30 ,In 0.2 ,Sc 0.2 ) 0.80 F6:0.20Cr 3+ , the specific preparation method is as follows:
[0151] According to the stoichiometric ratio, the corresponding raw materials were weighed: 0.4502 g Al(NO3)3·9H2O, 0.1125 g Ga2O3, 0.1110 g In2O3, 0.0552 g Sc2O3, 0.20 g Cr(NO3)3·9H2O, 0.2905 g KF and 8.3545 g CsF.
[0152] First, add Al(NO3)3·9H2O, Ga2O3, In2O3 and Sc2O3 into the reaction container, then add 5 mL HF, stir for 8 min, then add Cr(NO3)3·9H2O, continue stirring for 15 min, then add KF and the above solutions in sequence, and continue stirring at room temperature for 30 min.
[0153] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, and kept at 200°C for 10 h.
[0154] After the reaction was completed and cooled to room temperature, the green product was collected, washed three times with 25 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 70 ° C for 5 h. Finally, the high entropy sample was obtained, which was the near-infrared fluorescent material Cs2K (Al 0.30 ,Ga 0.30 ,In 0.2 ,Sc 0.2 ) 0.80 F6:0.20Cr 3+ , abbreviated as Cs2KMF6:0.20Cr 3+ .
[0155] High entropy sample Cs2KMF6:0.20Cr 3+ and single matrix Cs2KGa 0.80 F6:0.20Cr 3+ The emission spectrum of Figure 7 As shown in the figure, under 460nm excitation, both samples obtained a wide near-infrared emission band with a peak at ~775nm in the range of 650nm to 1100nm.3+ Medium Cr 3+ The symmetry of the crystal field environment of Cr is reduced. 3+ The radiative transition is enhanced, and the near-infrared emission of the high-entropy sample is increased by 98% compared with the single matrix.
[0156] The crystal structure of the high entropy sample is shown in Figure 8 , Cs2KM 0.80 F6:0.20Cr 3+ It belongs to the classic cubic double perovskite structure with a space group of Fm-3m. 3+ and K + By 6 F - Surrounding MF 6 and KF 6 Octahedral, and Cs + The ions are located in a cavity surrounded by eight GaF6 and KF6 octahedra, which are connected by cross-shared corners to form a three-dimensional network framework.
[0157] Example 8
[0158] This embodiment provides a near-infrared fluorescent material excited by blue light, and its chemical formula is: LiSr(Al 0.20 ,Ga 0.20 ,In 0.20 ,Gd 0.20 ,Sc 0.20 ) 0.85 F6:0.15Cr 3+ , the specific preparation method is as follows:
[0159] According to the stoichiometric ratio, the corresponding raw materials were weighed: 0.0433 g Al2O3, 0.0797 g Ga2O3, 0.1180 g In2O3, 0.0586 g Sc2O3, 0.1541 g Gd2O3, 0.6281 g SrF2, 0.1297 g LiF and 0.0817 g CrF3.
[0160] First, add Al2O3, Ga2O3, In2O3, Sc2O3 and Gd2O3 into the reaction container, then add 6 mL HF, stir for 20 min, then add CrF3, continue stirring for 5 min, then add SrF2 and LiF to the above solution in sequence, and continue stirring at room temperature for 20 min.
[0161] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus and kept at 200°C for 8 h.
[0162] After the reaction was completed and cooled to room temperature, the green product was collected, washed twice with 30 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 70 °C for 4 h to obtain a high entropy sample of LiSr(Al 0.20 ,Ga 0.20 ,In 0.20 ,Gd 0.20 ,Sc 0.20 ) 0.85 F6:0.15Cr 3+ , abbreviated as LiSrMF6:0.15Cr 3+ .
[0163] Example 9
[0164] This embodiment provides a near-infrared fluorescent material excited by blue light, and its chemical formula is: Li3Na3(Al 0.30 ,Ga 0.30 ,In 0.20 ,Sc 0.20 ) 1.91 F6:0.09Cr 3+ , the specific preparation method is as follows:
[0165] According to the stoichiometric ratio, the corresponding raw materials were weighed: 0.2406 g AlF3, 0.2685 g Ga2O3, 0.2651 g In2O3, 0.1317 g Sc2O3, 0.18 g Cr(NO3)3·9H2O, 1.9454 g LiF and 0.795 g Na2CO3.
[0166] First, AlF3, Ga2O3, In2O3 and Sc2O3 raw materials were added to the reaction container in sequence, followed by adding 5 mL of HF and mechanically stirring for 15 min. Cr(NO3)3·9H2O was then added and stirred for 5 min. Subsequently, LiF and Na2CO3 were added to the above solution and stirred at room temperature for 35 min.
[0167] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, where it was kept at 220°C for 14 h.
[0168] After the reaction was completed and cooled to room temperature, the green product was collected, washed three times with 25 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 65 °C for 6 h to obtain a high entropy sample of Li3Na3(Al 0.30 ,Ga 0.30 ,In 0.20 ,Sc 0.20 ) 1.91 F6:0.09Cr 3+ , abbreviated as Li3Na3 MF6:0.09Cr 3+
[0169] Example 10
[0170] This embodiment provides a near-infrared pc-LED device, which is prepared by packaging a high-entropy fluoride near-infrared phosphor and a commercial InGaN blue light LED chip, and its photoelectric parameters are tested to verify its application potential in the near-infrared field.
[0171] The Cs2Na(Al 0.25 ,Ga 0.25 ,In 0.25 ,Sc 0.25 ) 0.80 F6:0.20Cr 3+ High entropy fluoride near-infrared phosphor and epoxy resin are mixed evenly in a certain mass ratio (near-infrared phosphor: epoxy resin = 1:1). Then, the bubbles in the mixture are removed by a degassing machine to ensure the uniformity and stability of the mixture. Then, a professional glue coating equipment is used to evenly coat it on the surface of a blue light LED chip (3W, ~445nm). After coating, the chip is placed in a curing device and cured according to the set temperature and time. Then it is naturally cooled to room temperature to obtain a near-infrared pc-LED device (such as Figure 1 shown).
[0172] like Figure 1 The figure shows the near-infrared pc-LED device and its electroluminescence spectrum packaged in Test 10. As the driving current gradually increases, its near-infrared emission intensity increases monotonically, and no light saturation phenomenon is observed, indicating that it has broad application prospects in the near-infrared field.
[0173] Comparative Example 1
[0174] The near-infrared fluorescent material provided in this comparative example has the chemical formula: K3Al 0.92 F6:0.08Cr 3+ , the specific preparation method is as follows:
[0175] According to the stoichiometric ratio, the corresponding raw materials 1.7256 g Al(NO3)3·9H2O, 0.0436 g CrF3 and 2.905 g KF were weighed.
[0176] First, add Al(NO3)3·9H2O to the reaction container; then add 4 mL HF and stir for 4 min; then add CrF3 and continue stirring for 5 min; then add KF to the above solution and continue stirring at room temperature for 15 min.
[0177] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, and kept at 160°C for 12 h.
[0178] After the reaction was completed and cooled to room temperature, the green product was collected, washed twice with 25 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 65 °C for 6 h to obtain a single matrix control sample K3Al 0.92 F6:0.08Cr 3+ , abbreviated as K3AlF6:0.08Cr 3+ .
[0179] Comparative Example 2
[0180] The near-infrared fluorescent material provided in this comparative example has the chemical formula: Na3Sc 0.75 F6:0.25Cr 3+ , the specific preparation method is as follows:
[0181] According to the stoichiometric ratio, the corresponding raw materials 0.2586g Sc2O3, 0.0950g Cr2O3 and 3.1493g NaF were weighed.
[0182] First, add Sc2O3 to the reaction container; then add 6 mL HF and stir for 5 min; then add Cr2O3 and continue stirring for 15 min; then add NaF to the above solution and continue stirring at room temperature for 25 min.
[0183] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, and kept at 200°C for 10 h.
[0184] After the reaction was completed and cooled to room temperature, the green product was collected and washed three times with 25 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 60 °C for 8 h to obtain a single matrix control sample Na3Sc 0.75 F6:0.25Cr 3+ , abbreviated as Na3ScF6:0.25Cr 3+
[0185] Comparative Example 3
[0186] The near-infrared fluorescent material provided in this comparative example has a chemical formula of K2LiGa 0.90 F6:0.10Cr 3+ , the specific preparation method is as follows:
[0187] According to the stoichiometric ratio, the corresponding raw materials 0.4217g Ga2O3, 0.038g Cr2O3, 4.686g KHF2 and 0.1297g LiF were weighed.
[0188] First, add Ga2O3 to the reaction container; then add 5 mL HF and stir for 5 minutes; then add Cr2O3 and continue stirring for 10 minutes; then add KHF2 and LiF to the above solution in sequence and continue stirring at room temperature for 20 minutes.
[0189] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, and kept at 180°C for 10 h.
[0190] After the reaction was completed and cooled to room temperature, the green product was collected, washed three times with 25 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 65 °C for 8 h to obtain a single matrix control sample K2LiGa 0.90 F6:0.10Cr 3+ , abbreviated as K2LiGaF6:0.10Cr 3+ .
[0191] Comparative Example 4
[0192] The near-infrared fluorescent material provided in this comparative example has the molecular formula: Cs2NaGa 0.80 F6:0.20Cr 3+ , the specific preparation method is as follows:
[0193] According to the stoichiometric ratio, the corresponding raw materials 0.1874 g Ga2O3, 0.20 g Cr(NO3)3·9H2O, 0.1050 g NaF and 7.595 g CsF were weighed.
[0194] First, add Ga2O3 to the reaction container; then add 5 mL HF and stir for 5 min; then add Cr(NO3)3·9H2O and continue stirring for 5 min; then add NaF and CsF to the above solution in sequence and continue stirring at room temperature for 40 min.
[0195] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, where it was kept at 200°C for 18 h.
[0196] After the reaction was completed and cooled to room temperature, the green product was collected, washed three times with 30 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 70 °C for 6 h to obtain a single matrix control sample Cs2NaGa 0.80 F6:0.20Cr 3+ , abbreviated as Cs2NaGaF6:0.20Cr 3+ .
[0197] Comparative Example 5
[0198] The near-infrared fluorescent material provided in this comparative example has the molecular formula: LiSrAl 0.85 F6:0.15Cr3+ , the specific preparation method is as follows:
[0199] According to the stoichiometric ratio, the corresponding raw materials 0.2167 g Al2O3, 0.30 g Cr(NO3)3·9H2O, 0.6281 g SrF2 and 1.9454 g LiF were weighed.
[0200] First, add Al2O3 to the reaction container; then add 6 mL HF and stir for 10 min; then add Cr(NO3)3·9H2O and continue stirring for 5 min; then add SrF2 and LiF to the above solution in sequence and continue stirring at room temperature for 20 min.
[0201] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, and kept at 200°C for 10 h.
[0202] After the reaction was completed and cooled to room temperature, the green product was collected, washed three times with 20 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 70 °C for 4 h to obtain the single matrix control sample LiSrAl 0.85 F6:0.15Cr 3+ , abbreviated as LiSrAlF6:0.15Cr 3+ .
[0203] Comparative Example 6
[0204] The near-infrared phosphor provided in this comparative example has the chemical formula: Li3Na3Al 1.91 F6:0.09Cr 3+ , the specific preparation method is as follows:
[0205] According to the stoichiometric ratio, the corresponding raw materials were weighed into 1.7068 g Al(NO3)3·9H2O, 0.049 g CrF3, 0.6299 g NaF and 1.9454 g LiF.
[0206] First, Al(NO3)3·9H2O was added to the reaction container, followed by 4 mL of HF, and stirred for 5 min. CrF3 was then added, and stirring continued for 5 min. NaF and LiF were then added to the above solution in sequence, and stirring continued for 20 min at room temperature.
[0207] The reaction vessel was then placed in an autoclave and transferred to a reaction apparatus, where it was kept at 220°C for 14 h.
[0208] After the reaction was completed and cooled to room temperature, the green product was collected and washed three times with 25 mL of acetic acid and anhydrous ethanol respectively, and finally dried in a drying oven at 75 °C for 4 h to obtain a single matrix control sample: Li3Na3Al 1.91 F6:0.09Cr3+ , abbreviated as Li3Na3AlF6:0.09Cr 3+ .
[0209] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A near-infrared fluorescent material excited by blue light, characterized in that: Including the chemical formula A2BM 1-x F6:xCr 3+ 、ACM 1-x F6:xCr 3+ and A3B3M 2-x F 12 :xCr 3+ At least one compound of The A position includes at least one of a monovalent alkali metal element and an ammonium group; The B position includes at least one of a monovalent alkali metal element and an ammonium group; The C position includes at least one of the divalent alkaline earth metal elements; The M position includes at least four elements of Zn, Mg, Al, Ga, Sc, In, Ti, Zr, Hf, Sn, Ge, Y, Gd, La, Lu and Sb; the molar percentage of each element included in the M position is close, and the molar percentage of each element is in the range of 5% to 35%; 0.01≤x≤0.35。 2. The blue light excited near-infrared fluorescent material according to claim 1, characterized in that: Satisfy at least one of the following (1) to (5): (1) The monovalent alkali metal element in the A position includes at least one of Li, Na, K, Rb and Cs; (2) the monovalent alkali metal element in the B position includes at least one of Li, Na, K, Rb and Cs; (3) the ammonium group in the A position includes at least one of an ammonium radical group and a tetramethylammonium group, (4) the ammonium group in the B position includes at least one of an ammonium radical group and a tetramethylammonium group; (5) The divalent alkaline earth metal element includes at least one of Ca, Sr, Ba, Mg and Zn.
3. The blue light excited near-infrared fluorescent material according to claim 1 or 2, characterized in that: The molar percentage of each element contained in the M position differs within 10%.
4. The blue light excited near-infrared fluorescent material according to claim 1, characterized in that: The wavelength of the excitation light of the near-infrared fluorescent material excited by blue light is 420nm-470nm; and / or the wavelength of the emission light is 700nm-1000nm.
5. A method for preparing a near-infrared fluorescent material excited by blue light, characterized in that: The following steps are involved: Obtaining raw material components according to the stoichiometric ratio of the chemical formula in the blue light excited near-infrared fluorescent material according to any one of claims 1 to 4; the raw material components include Cr element raw material components, M-position raw material components and A-position raw material components, and also include B-position raw material components and / or C-position raw material components; The raw material components are subjected to hydrothermal treatment to prepare a near-infrared fluorescent material excited by blue light.
6. The method for preparing a near-infrared fluorescent material excited by blue light according to claim 5, characterized in that: The raw material components satisfy at least one of the following (1) to (5): (1) The Cr element raw material component includes at least one of chromium chloride, chromium nitrate, chromium hydroxide, chromium fluoride and chromium oxide; (2) The M-position raw material component includes at least one of an oxide, a fluoride and a metal salt; (3) The A-site raw material component includes: at least one of a fluoride and a carbonate; (4) The B-site raw material component includes: at least one of fluoride and carbonate; (5) The C-site raw material component includes at least one of fluoride and carbonate.
7. The method for preparing a near-infrared fluorescent material excited by blue light according to claim 5, characterized in that: The solvent used in the hydrothermal treatment includes a fluorine-containing acidic aqueous solution.
8. The method for preparing a near-infrared fluorescent material excited by blue light according to claim 5, characterized in that: The control parameters in the hydrothermal treatment step include: The temperature of the hydrothermal treatment is 160° C. to 240° C., and / or the time of the hydrothermal treatment is 6 h to 24 h.
9. The method for preparing a near-infrared fluorescent material excited by blue light according to any one of claims 5 to 8, characterized in that: The step of subjecting the raw material components to hydrothermal treatment comprises: First, the M-position raw material component and the solvent used in the hydrothermal treatment are mixed; then the Cr element raw material component is added and mixed; then the A-position raw material component and at least one of the B-position raw material component and the C-position raw material component are added and mixed to obtain a mixed material; The mixed material is subjected to hydrothermal treatment.
10. A light emitting device, characterized in that: It comprises a light source and a luminescent material excited by the light source, wherein the luminescent material comprises the near-infrared fluorescent material excited by the blue light as described in any one of claims 1 to 4, or comprises the near-infrared fluorescent material excited by the blue light obtained by the preparation method as described in any one of claims 5 to 9.
Citation Information
Patent Citations
Novel Cr < 3 + > doped fluoride near-infrared fluorescent powder and preparation method thereof
CN113265242A
Cr<3+>-doped novel fluoride near-infrared fluorescent material, and preparation method and luminescent source thereof
CN113444522A
Fluoride near-infrared luminescent material as well as preparation method and application thereof
CN114686223A
Novel Mn < 4 + > and Cr < 3 + > co-doped fluoride near-infrared fluorescent powder and preparation method thereof
CN116285965A
